Jaundice in adult patients above 50 years of age: a comparative study of liver function tests - Chauhan, Suneel; Barwal, Vijay Kumar; Sharma, Gopal A.; Vaid, Ajay; Sood, Nikhil; Rana, Naveen (International Journal of Research in Medical Sciences, 2020)
Background: Diagnosis of jaundice involves a range of tests. The liver function tests are done in all to arrive at a diagnosis and then manage the case appropriately. With advancing age, the incidence of liver disease increases. Understanding these changes is important for the management of liver diseases in the elderly. We conducted this study to find the difference in mean levels of Liver enzymes in younger and older age group of patients suffering with jaundice. Methods: It was a prospective observational study. All patients admitted with jaundice in the medicine ward satisfying inclusion/exclusion criteria were enrolled. The results of liver function tests in younger age and older age participants were then compared. Results: Total 100 participants were enrolled during the study period. 53 were enrolled in group one and the rest in group two. Anorexia (90%) was the most common symptom followed by abdominal distension (54%). The total bilirubin (8.8±4.7) as well as conjugated bilirubin (3.4±2.8) were higher in group one though they were not significant statistically (p=0.10 and 0.25 respectively). Mean AST and ALT levels were much higher in group 1 and statistically significant (p values <0.004 and 0.002 respectively). Conversely the mean PT values were higher in group two (p=0.02). Conclusions: Although the symptom severity may be more in elderly, the LFTs are not deranged proportionately. So there is a need to devise separate cut offs and these have to be lower for the older age group patients with jaundice. More studies with larger sample size are required to confirm the results.